South Africa and Sweden in the UN Security Council - Angela Muvumba Sellström; Suzanne Graham (The Thinker)
The UN Security Council is the world’s most established forum for safeguarding international peace and security. It has, however, suffered from significant deficiencies in legitimacy and effectiveness. The permanent five (P5) members control the Council’s agenda and block action on conflicts because of their own national interests and geopolitical rivalries. New research (see Graham, 2022; Olsson, Muvumba Sellström, and Chang, 2021; and for example, Bode, 2018; Pay and Postolski, 2022; and Farrall, Loisell and Prantl, 2020) suggests that the elected ten (E10) members are, however, able to project their own interests and preferences, and shape decisions from inside the Council, particularly on conflict situations and themes that affect Africa. Indeed, conflict in Africa makes up two-thirds of the Council’s workload, and 85% of UN military peacekeepers are deployed to the continent. This short article explores the recent memberships of Sweden (2017-18) and South Africa (2019-20). Elected states have played an active role in terms of promoting cross-cutting themes, including strengthening Africa’s Peace and Security Architecture (APSA) and the women, peace, and security (WPS) agenda, to varying degrees. Elected members can distinguish their short tenures on the Council by signalling their contribution to global affairs through thematic events and resolutions. By presenting South Africa and Sweden’s record of conduct on these themes, the article explores differences and similarities in E10 practice. The main contribution is an illustration of how elected states pursue a common agenda, using diverse methods of engagement. This variation is important for understanding the UNSC, since it demonstrates the Council’s pluralist nature, and the interplay of its least powerful members through policy practices of specialization and interdependence.